PENGARUH DANA BERGULIR TERHADAP KINERJA UMKM DI KOTA PADANG PANJANG SUMATRA BARAT - Musbatiq Srivani; Erizal Nurdin; Amra Ausri (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
Micro, small and medium micro businesses are mainly Indonesia's economic liberalization. Bank Indonesia bi governor burhanudin abdullah said here on Tuesday the central bank had decided to raise its benchmark interest rate by 25 basis points to 8.25 percent. The alternative to this problem is the Revolving Funds. It is a city in which most seek out small businesses, food costs, clothing, or daily necessities is Padang Panjang, West Sumatra which has a basic problem of capital with the existence of this Revolving Fund which can increase the performance of UMKM in the city of Padang Panjang. The research aims to find out how ineja umkm after getting loans from Revolving Funds, with a dar ampel population of 98 people and using a sampling census technique. The data processing method USES the wilcoxon test to generate significant significant differences... and the umkm to acquire a rolling fund loan.